Gut bacteria are essential for normal cuticle development in herbivorous turtle ants - Christophe Duplais (Nature Portfolio, 2021)
Microbial symbionts can help their hosts metabolise diverse diets. A study on herbivorous turtle ants identifies the cuticular components which are nitrogen-enriched by gut bacteria, highlighting the role of symbionts in insect evolution.